Surgical tactics for nodular thyroid diseases with compression syndrome - V.V. Boyko; V.V. Kritsak; A.L. Sochnieva; V.V. Tkachenko (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. Clinical manifestations of tracheal compression occur when its lumen is narrowed by more than 70 %. When using spirometry as a screening method, the frequency of upper airway obstruction was from 10 to 31 %. Timely and adequate surgical treatment of patients with substernal goiter leads to the complete disappearance of symptoms of tracheal compression and reduces mortality. The purpose of the study is to analyze surgical tactics in nodular thyroid diseases with compression syndrome. Materials and methods. We operated on 167 patients for urgent indications. The cause for admission to the hospital was compression syndrome of the neck organs (trachea) due to compression or growth of thyroid tumors. Differentiated thyroid cancer was the cause of compression syndrome in 79 (47.3 %) patients. In 88 (52.7 %) cases, compression was caused by multinodular euthyroid cervicothoracic goiter. In 52 (31.1 %) cases, patients underwent emergency surgery within the first day. These patients were included in the first study group. The second group included 115 (68.9 %) people. In them, conservative therapy was used to stabilize the condition, postpone the operation for 2–3 days, and perform emergency surgery. Results. Determination of the forced expiratory volume in one second (FEV1) in patients with severe tracheal narrowing due to compression by the altered thyroid gland and the risk of asphyxia objectively reflects the degree of tracheal narrowing and allows determining the timing of surgery, which is especially important for severely ill patients and elderly people with manifestations of concomitant pathology. When patients are admitted to the hospital with progressive shortness of breath and the threat of asphyxia due to tracheal compression by a goiter, the fastest possible determination of treatment strategy allows saving life and, subsequently, improving the prognosis for life and health. Conclusions. The division of surgical interventions into urgent ones with FEV1 from 35 to 54 % and urgent ones with FEV1 less than 35 % is of practical importance for preparing patients for aggressive treatment methods. During urgent operations, there is a possibility of correcting violations of vital functions of organs and systems, which affect the immediate and long-term results of surgical treatment.